Analisis Komparatif: Apakah Ada Perbedaan Kinerja Finansial Korporasi Sektor Non Keuangan di BEI Pra dan Pasca Merger Akuisisi? - Septiliani, Adelia; Anita Sari, Dian (Jurnal Manajemen dan Organisasi, 2025)
This research is intended to assess whether there are significant changes in the financial performance of non-financial companies on the Indonesia Stock Exchange before and after a merger or acquisition. Financial performance is tested using four financial indicators, namely liquidity ratio, solvency, profitability and activity. Data were analyzed by applying the paired sample t-test for data that was considered normal and while data was considered not normally distributed using the Wilcoxon signed ranks test. Data is collected with documentation. Data comes from secondary data. The data type uses documentary. The research sample consisted of 11 non-financial companies that carried out mergers and acquisitions in the 2016-2020 period and were listed on the Indonesian Stock Exchange. Purposive sampling technique was used in sampling. The time interval chosen in this research is three years before the merger or acquisition and three years after the merger or acquisition. From the study results, it was found that there were differences in the CR, DER and TATO ratios before or after mergers and acquisitions, while there was no change in the ROA ratio pre-implementation and post-implementation of mergers and acquisitions.